(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dentists of different specialties are sought for their expert testimony in person identification, injury related to oral and dental structures. Person identification may include live or dead, injured or healthy, skeletonized, or mummified. Dentists also opine in crime scene investigation, mass disaster victim identification, and professional negligence or injury. The dental surgeon evaluates the available dental evidence and drafts a report to testify in a deposition as a professional opinion in the medico-legal cases. This article discusses the demeanor of the dental surgeon as an expert in the court of law.